Evaluation of ventilation, indoor air quality, and probability of viral infection in an outdoor dining enclosure. Issue 5 (4th May 2022) - Persing, Allison J.; Roberts, Benjamin; Lotter, Jason T.; Russman, Eric; Pierce, Jennifer
Abstract: In 2020, many cities closed indoor dining to curb rising COVID-19 cases. While restaurants in warmer climates were able to serve outdoors year-round, restaurants in colder climates adopted various solutions to continually operate throughout the colder months, such as the use of single-party outdoor dining enclosures to allow for the continuation of outdoor dining. This study evaluates indoor air quality and the air exchange rate using carbon dioxide as a tracer gas in a dining enclosure (12.03 m 3 ) and models the probability of COVID-19 infection within such an enclosure. The air exchange rates were determined during two trials for the following scenarios: (1) door closed, (2) door opened, and (3) door opened intermittently every 15 min for 1 min per opening. The probability of COVID-19 infection was evaluated for each of these scenarios for 1 hr, with occupancy levels of two, four, and six patrons. The Wells–Riley equation was used to predict the probability of infection inside the dining enclosure. The air exchange rates were lowest in the closed-door scenarios (0.29–0.59 ACH), higher in the intermittent scenarios (2.36–2.49 ACH), and highest in the open-door scenarios (3.61 to 33.35 ACH). As the number of subjects inside the enclosure increased, the carbon dioxide accumulation increased in the closed-door and intermittent scenarios. There was no identifiable accumulation of carbon dioxide in the open-door scenario. The probability of infection (assuming one infected person without a mask) was inversely proportional to the airflow rate, and ranged from 0.0002–0.84 in the open-door scenario, 0.0034–0.94 for the intermittent scenarios, and 0.015–1.0 for the closed-door scenarios. The results from this study indicate that under typical use, the indoor air quality inside dining enclosures degrades during occupancy. The probability of patrons and workers inside dining enclosures being infected with COVID-19 is high when dining or serving a party with an infected person.